Social movements in contemporary India / Krishna Menon and Ranjana Subberwal. - Menon, Krishna; Subberwal, Ranjana (Routledge, 2025)
This is an interdisciplinary text that offers a comprehensive understanding of social movements, their cause, course and effects in modern-day India. Contemporary India is experiencing widespread changes and developments in its society, polity and economy, resulting in a variety of social movements in recent years. This textbook offers an understanding of these movements, issues, and discourses around them, and relates them to the wider society and resultant changes occurring within it.